2010
DOI: 10.1111/j.1600-0668.2009.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to indoor air pollution and wheezing symptoms in infants

Abstract: Long-term exposure to air pollution is suspected to cause recurrent wheeze in infants. The few previous studies have had ambiguous results. The objective of this study was to estimate the impact of measured long-term exposure to indoor air pollution on wheezing symptoms in infants. We monitored wheezing symptoms in diaries for a birth cohort of 411 infants. We measured long-term exposure to nitrogen oxides (NO(x)), NO(2), formaldehyde, PM(2.5) and black smoke in the infants' bedrooms and analyzed risk associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
1
36
2
4
Order By: Relevance
“…The majority (n=45) of studies employed observational designs. There were six cohort studies [31][32][33][34][35][36] and 11 case-control studies [37][38][39][40][41][42][43][44][45][46][47]. Among the observational studies, two-thirds (n=28) were cross-sectional studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (n=45) of studies employed observational designs. There were six cohort studies [31][32][33][34][35][36] and 11 case-control studies [37][38][39][40][41][42][43][44][45][46][47]. Among the observational studies, two-thirds (n=28) were cross-sectional studies .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies, including one RCT [23], three cohort studies [33][34][35] and one case-control study [47], were graded as being at low risk of bias; 15 studies, including two cohort studies [31,36], five case-control studies [37,[42][43][44][45] and eight cross-sectional studies [48,50,62,65,[72][73][74][75], were graded as being at moderate risk of bias. The remaining 33 studies were judged to be at high risk of bias (tables S1 and S1A).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the few studies to examine infants’ exposure in to indoor air pollution in homes in an industrialized country measured long-term exposure to NO x , NO 2 , formaldehyde, PM 2.5 , and black smoke in homes of 411 infants in Denmark, finding no association with risk of wheezing [55]. Raaschou-Nielsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In both urban and rural environments, this study (32) demonstrated that exposure to acetaldehyde and toluene was significantly associated with a higher risk of asthma (OR: 2.73, 95% CI: 1.28 -5.83, and OR: 2.15, 95% CI: 1.01-4.58, respectively). A long-term study of an infant cohort by Raaschou-Nielsen et al (58) explored the effects of exposure to indoor air pollution and wheezing, a symptom that may progress into asthma later in life. This study did not demonstrate a systematic association between the risk for wheezing symptoms and levels of indoor air pollutants.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%